Return of the werewolf - Martin, Les, 1934-; Chandler, Karen (New York : Random House, 1993)
Smitten with a beautiful countess, Sherlock Holmes's cousin agrees to unmask the killer who's been savaging her ancestral village.
Keywords: Werewolves -- Fiction; Horror stories